The development of a morphometric model for the estimation of mean annual sediment yield in ungauged catchments of South African river systems - Roberts, Peter J T (Rhodes University, Faculty of Science, Department of Geography, 1975)
Hydrologists are regularly faced with the unenviable task of having to predict the magnitude and frequency of phenomena such as floods and droughts; and rates of erosion. If long records are available for analysis the hydrologist is able to base his predictions on the premise that the pattern of variation that has been observed in the past will persist in the future. The confidence that can be placed in any estimate consequently depends to a large extent on the length of time over which the phenomena have been measured at the problem site. Unfortunately the availability of adequate records tends to be the exception rather than the rule and in areas where there is inadequate data, it is necessary to resort to the hazardous procedure of transferring information from the gauged to the ungauged catchments. The transfer of information is accomplished by using empirical methods based on regionalised parameters, but the uncertainties involved together with the economic implications that could arise from a poor estimate, prompt the hydrologist to use as many methods as possible. The need for empirical methods of estimating mean annual sediment yield in ungauged catchments was first appreciated by the author when he was involved in the estimation of design floods and sediment accumulation at sites for proposed reservoirs. Empirical methods of estimating sediment yield are frequently used in an engineering context, but little attention has been given to the catchment surface from which the sediment supply is derived. It is perhaps in this often neglected field of research that the physical geographer can make a contribution. The principal aim of the thesis, more fully discussed in Chapter I, was the development of a morphometric model which could be used to estimate mean annual sediment yield in ungauged catchments in South Africa. The data used in the development of the model were drawn from the catchments, described in Appendix A, that cover a wide range of climate and topography. A description of the approaches adopted by other researchers for the development of empirical models of estimating sediment yield which forms the background to the model has been included as Appendix B. The model was first developed in an elementary form as the focus of a research project which was documented in the form of three reports of research in progress (Roberts, 1973 a, b and c). Analysis of the pattern of variation of suspended sediment yield provided a better understanding of factors affecting sediment yield and supported the selection of the prediction variable (Horton's P ratio) which was used in the model. The concepts of network topology were utilised to gain insight into the environmental factors controlling both the P ratio and sediment yield. Reasons for the high correlation between the P ratio and sediment yield are suggested but it is felt that further research should be focused on this aspect. In order not to break the continuity and development of the steps taken in the derivation of the model details of the calculations are collected in Appendices C, D and E. While many of the figures and tables presented in the thesis appeared in technical notes prepared entirely by the author for the Department of Water Affairs, the views expressed in the thesis do not in any way, either explicitly or by implication, represent any official view or policy of the Department of Water Affairs.
Keywords: Sedimentation and deposition -- South Africa -- Mathematical models